Sistem Pelayanan Surat Administrasi Masyarakat Gampong Berbasis Webbase dengan menggunakan Framework CodeIgniter - Munawir Munawir; Susmanto Susmanto; Zulfan Zulfan; Yeni Yanti (Fakultas Teknik, 2020)
Service Standards are benchmarks that are used as guidelines for service delivery and references as a Service Standards are benchmarks used as quality assessment guidelines service to the community as a quality service, fast, easy, affordable, and measurable. At this time the development of technology and information systems increasingly stringent so that it requires the readiness of a technology that is able to answer competition in the government environment. Service data processing information systems in Gampong currently do not meet technological development standards in the present, because the existing data processing systems are still done manually using MS. Word and MS. EXCEL. The problem of service if you make a letter by hand is that the people who make the letter have to wait a long time, so the village officials must input the data manually. The purpose of this research is to produce a system in serving the public to make the documents needed by the community, so that the officers can provide services quickly and accurately. of the Village Administration, with the existence of this information system can provide services in the village administration data collection that previously was still using the manual system method.